APPLICATION OF PLAYING METHOD MOBIS TO GROW-BUILD A FINE MOTORIC SKILL AND CREATIVITY OF PRESCHOOL AGE (5-6 years) THROUGH MOBILE ACTIVITIES IN ISLAMIC KINDERGARTEN AN-NISA BANDUNG - efie muf tiati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
AbstractImplementation of play methods in early childhood has always been a major effort in foster-growinga fine motor skills and creativity. In An-Nisa Bandung kindergarten, the method of playing through Mobis (Motor skills block interlocking system) activities is applied to 20 B-age group students aged 5-6 years to know the success rate of developing motor skills and creativity after 8 times of monitoring in the class. The results of the experimental experiments show a smooth growth rate of fine motor skills average of 70% or included in the category "Growing as the hope" and the average creativityof 85 % which belongs to the category "Growing very good". Evaluation of the effectiveness of Mobis method implementation shows more correction or refinement result about parameters of the number of applications within the specified time period that best suits the psychological situation of the students. The other improvements are statistically mainly about the number of students who should be more and come from various backgrounds of family culture, as well as supporting facilities in class activities and the number of teachers and teacher assistants who monitor.